Minimally invasive aortic valve surgery in obese patients: Can the bigger afford the smaller?. Issue 2 (20th December 2020) - Mikus, Elisa; Calvi, Simone; Brega, Carlotta; Zucchetta, Fabio; Tripodi, Alberto; Pin, Maurizio; Manfrini, Marco; Cimaglia, Paolo; Masiglat, Joyce; Albertini, Alberto
Abstract: Background: Ministernotomy and right minithoracotomy are well‐known minimally invasive approaches for aortic valve replacement (AVR); however, controversial opinions exist for their utilization in obese patients. The aim of this study is to check a potential positive role of minimally invasive surgery in this population. Methods: From January 2010 to November 2019, 613 obese patients (defined by a body mass index ≥30) underwent isolated AVR at our institution. Surgical approach included standard median sternotomy (176 patients), partial upper sternotomy (271 patients), or right anterior minithoracotomy (166 patients). Intra‐ and postoperative data were retrospectively collected. Results: Patients treated with minimally invasive approaches had shorter cardiopulmonary bypass time ( p = .012) and aortic cross‐clamp time ( p = .022), mainly due to the higher utilization of sutureless valve implantation. They also presented advantages in terms of reduced postoperative ventilation time ( p = .010), incidence of wound infection ( p = .009), need of inotropic support ( p = .004), and blood transfusion ( p = .001). The univariable logistic regression showed the traditional full sternotomy approach as compared with ministernotomy ( p = .026), active smoking ( p = .009), peripheral vascular disease ( p = .003), ejection fraction ( p = .026), as well Logistic European system for cardiac operative risk evaluation (EuroSCORE; p = .015) as factors associated with hospital mortality. The multivariable logistic regression adjusted for the logistic EuroSCORE revealed that surgical approaches do not influence hospital mortality. Conclusions: Obese patients with severe aortic valve pathology can be treated with minimally invasive approaches offering a less biological insult and reduced postoperative complications, but without impact on hospital mortality.